2013
DOI: 10.7589/2012-05-124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neutralizing Antibodies to Rabies Virus in Serum of Seven Species of Insectivorous Bats From Colorado and New Mexico, United States

Abstract: ABSTRACT:We determined the presence of rabies-virus-neutralizing antibodies (RVNA) in serum of 721 insectivorous bats of seven species captured, sampled, and released in Colorado and New Mexico, United States in [2003][2004][2005]. A subsample of 160 bats was tested for rabies-virus RNA in saliva. We sampled little brown bats (Myotis lucifugus) at two maternity roosts in Larimer County, Colorado; big brown bats (Eptesicus fuscus) at three maternity roosts in Morgan County, Colorado; and big brown bats at five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
(45 reference statements)
5
11
1
Order By: Relevance
“…Seroprevalence among collection sites ranged from 0 to 21% among all bats, and 0 to 25% for D. rotundus , respectively. Our results are concordant with previous studies in demonstrating that a substantial fraction of apparently healthy bats have detectible rVNA, indicating previous exposure to RABV, and suggesting clearance of peripheral infection without clinical disease [42][44]. The presence of rVNA only demonstrates prior exposure to RABV antigens, and does not provide information about the timing, intensity, or frequency of infection [45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Seroprevalence among collection sites ranged from 0 to 21% among all bats, and 0 to 25% for D. rotundus , respectively. Our results are concordant with previous studies in demonstrating that a substantial fraction of apparently healthy bats have detectible rVNA, indicating previous exposure to RABV, and suggesting clearance of peripheral infection without clinical disease [42][44]. The presence of rVNA only demonstrates prior exposure to RABV antigens, and does not provide information about the timing, intensity, or frequency of infection [45].…”
Section: Discussionsupporting
confidence: 90%
“…The detection of rVNA from bats in this study demonstrated RABV exposure among multiple species of bats in Guatemala. The overall rVNA prevalence of 7% was similar to other bat RABV surveillance studies conducted in Peru (10.3%), Grenada (7.6%) and Trinidad (12.8%), but less than the 37% detection in Colima, Mexico [42][44]. Seroprevalence among collection sites ranged from 0 to 21% among all bats, and 0 to 25% for D. rotundus , respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Oropharyngeal secretions of bats were sampled at the laboratory using cotton-tipped swabs inserted into 0.5 ml of BA-1 medium (Minimal Essential Medium with Hanks’ balanced salt solution containing 0.05 M Tris buffer at pH 7.6, 1% Bovine Serum Albumin, 0.35 g/L of Sodium bicarbonate, 50 mg/L Gentamicin, and 2.5 mg/L Amphotericin B). Serum and oropharyngeal swabs were frozen at −80 C until shipment to the Centers for Disease Control and Prevention (CDC), Atlanta, Georgia for testing [17], [50]. Capture, marking, sampling, and euthanasia of bats were approved by the Institutional Animal Care and Use Committees of Colorado State University and the United States Geological Survey.…”
Section: Methodsmentioning
confidence: 99%
“…Seroprevalence at other roosts that were sampled only in 2003 are reported elsewhere [50]. We use study numbers for roosts listed in summary statistics, but to protect confidentiality of building owners and occupants we do not provide details of roost locations or names.…”
Section: Methodsmentioning
confidence: 99%
“…This result is similar to the 7.4% positivity rate found among hematophagous bats 14 in Botucatu, State of São Paulo, and higher than the 5.9% seroprevalence rate observed in the metropolitan São Paulo region for bats of a variety of species, including hematophagous bats 12 . Serological studies have been conducted in bats and terrestrial wild species in Brazil and other countries as a means of determining the risk of rabies occurrence and the need for RABV surveillance 14,[31][32][33][34][35] . All of these studies detected the presence of RVNAs; although the OIE recommends the standardization of serological techniques for the detection of RVNAs 36 , seroprevalence studies conducted using a variety of methods are still important tools for investigating viral activity levels in wild populations.…”
Section: Ethical Considerationsmentioning
confidence: 99%